Efficacy and Safety of a Novel Dual Modulator of Adenosine Triphosphate-Citrate Lyase and Adenosine Monophosphate-Activated Protein Kinase in Patients With Hypercholesterolemia - Ballantyne, Christie M.; Davidson, Michael H.; MacDougall, Diane E.; Bays, Harold E.; DiCarlo, Lorenzo A.; Rosenberg, Noah L.; Margulies, Janice; Newton, Roger S. (Journal of the American College of Cardiology, 2013)
The aim of this study was to assess the lipid-altering efficacy and safety of ETC-1002 in subjects with hypercholesterolemia. ETC-1002 is a small molecule that modulates pathways of cholesterol, fatty acid, and carbohydrate metabolism and may have therapeutic benefits in treating hypercholesterolemia and other cardiometabolic risk factors. This multicenter, randomized, double-blind, placebo-controlled, parallel-group trial evaluated patients (n = 177) with elevated low-density lipoprotein cholesterol (LDL-C) (130 to 220 mg/dl), who were stratified by baseline triglycerides (not elevated [<150 mg/dl] or elevated [150–<400 mg/dl]) and randomized to receive 40, 80, or 120 mg of ETC-1002 or placebo once daily for 12 weeks. Outcomes included changes in LDL-C (primary endpoint), other lipids, and cardiometabolic risk factors; and safety. ETC-1002 40, 80, and 120 mg lowered least-squares mean ± SE LDL-C levels by 17.9 ± 2.2%, 25.0 ± 2.1%, and 26.6 ± 2.2%, respectively, versus a reduction of 2.1 ± 2.2% with placebo (all, p < 0.0001); LDL-C lowering was similar between the subgroups with nonelevated and elevated triglycerides. ETC-1002 also lowered non–high-density lipoprotein cholesterol (non–HDL-C), apolipoprotein B, and LDL particle number (all, p < 0.0001) in a dose-dependent manner; HDL-C and triglyceride levels were relatively unchanged. Post-hoc analyses suggest that ETC-1002 may have favorable effects on other cardiometabolic risk factors. The ETC-1002 and placebo groups did not demonstrate clinically meaningful differences in adverse events or other safety assessments. ETC-1002 significantly lowered LDL-C levels up to 27% across a broad range of baseline triglycerides and was generally safe and well tolerated. ETC-1002 has a novel mechanism of action and may be useful for reducing LDL-C. (A Study to Assess the Efficacy and Safety of ETC-1002 in Subjects With Elevated Blood Cholesterol and Either Normal or Elevated Triglycerides; NCT01262638)